Air pollution from household solid fuel combustion in India: an overview of exposure and health related information to inform health research priorities - Kalpana Balakrishnan; Padmavathi Ramaswamy; Sankar Sambandam; Gurusamy Thangavel; Santu Ghosh; Priscilla Johnson; Krishnendu Mukhopadhyay; Vidhya Venugopal; Vijayalakshmi Thanasekaraan (Taylor & Francis Group, 2011)
Environmental and occupational risk factors contribute to nearly 40% of the national burden of disease in India, with air pollution in the indoor and outdoor environment ranking amongst leading risk factors. It is now recognized that the health burden from air pollution exposures that primarily occur in the rural indoors, from pollutants released during the incomplete combustion of solid fuels in households, may rival or even exceed the burden attributable to urban outdoor exposures. Few environmental epidemiological efforts have been devoted to this setting, however. We provide an overview of important available information on exposures and health effects related to household solid fuel use in India, with a view to inform health research priorities for household air pollution and facilitate being able to address air pollution within an integrated rural–urban framework in the future.